AB0807 Cardiovascular Risk Factors and Cardiovascular Disease in Psoriatic Arthritis. (9th June 2015) - Hoiberg, H.K.; Semb, A.G.; Diamantopoulos, A.P.; Kavanaugh, A.; Haugeberg, G.
Abstract : Background: Patients with rheumatoid arthritis (RA) are at increased risk for cardiovascular disease (CVD) (1). In psoriatic arthritis (PsA) the data is less conclusive but seem to favor an increased risk of CVD (2). Objectives: To explore the presence of CVD risk factors and CVD in PsA patients and potential associates with CVD. Methods: PsA patients fulfilling the CASPAR criteria, visiting an outpatient clinic from January 2013 to May 2014 were included. Patients with axial manifestation without peripheral arthritis were excluded. A systematic data collection was performed including demographics, disease activity, health status measures, treatments for PsA, relevant comorbidities, CVD medication, traditional and novel CVD risk factors which were tested in univariate and multivariate logistic regression models for their associations with the presence of CVD. Relevant variables in univariable analysis with a p value <0.2 were brought into a multivariate model. Results: Among the 141 included PsA patients (men 50.4%) mean (SD) age was 52.5 (10.0) years, body mass index (BMI) 28.3 (4.4) kg/m 2, disease duration 8.9 (6.8) years and DAS28 3.17 (1.15). Median [IQR] for CRP was 2.0 [4.0] mg/dl, PASI 1.1 [3.0] and MHAQ 0.38 [0.62]. Current use of biological disease modifying anti rheumatic drugs (b-DMARDs) was 33.6%, synthetic DMARDs (s-DMARDs) 56.7%, glucocorticosteroids 9.9%, non-steroid anti-inflammatory drugs (NSAIDs) 32.4%. The prevalence of current smoking was 17.2%, self-reported hypertension 31.2%, family history of CVD 18.4% and diabetes mellitus (DM) 8.5%. A total of 24.1% used cholesterol lowering agents and 11.3% aspirin. 9 patients (6.4%) had CVD defined as either myocardial infarction (MI) (n=7), percutaneous coronary intervention/coronary artery bypass graft (PCI/CABG) (n=9), or both. In an adjusted logistic regression analysis including relevant associates tested in univariate analysis only DM Odds ratio (OR), 4.4 (p=0.03) and family history of CVD 5.8 (p=0.01) was independently associated with present CVD. Whereas s-DMARDs (p=0.05), disease duration (p=0.07) and self-reported hypertension (p=0.06) were borderline significantly associated with present CVD. The results remained stable after adjusting for age and BMI. Conclusions: In this PsA cohort only 6.4% of the patients had CVD defined as MI or PCI/CABG, which is lower than a previous reported (14%)(3). DM and family history of CVD were found to be associated with CVD in our cohort. References: Christina Charles-Schoeman. Cardiovascular Disease and Rheumatoid Arthritis: An Update. Curr Rheumatol Rep (2012) 14:455–462 Katsiki N, Anagnostis P, Athyros VG, Karagiannis A, Mikhailidis DP 1 . Psoriasis and Vascular Risk: an Update. Curr Pharm 2014 Apr 16. Epub ahead of print. Epub 2014 Jan 30 Favarato MH, Mease P, Gonçalves CR, Gonçalves Saad C, Sampaio-Barros PD, Goldenstein-Schainberg C. Hypertension and diabetes significantly enhance the risk of cardiovascular disease in patients with psoriatic arthritis. Clin Exp Rheumatol. 2014 Mar-Apr;32(2):182-7. Epub 2014 Jan 30 Acknowledgements: Unrestricted grant from Pfizer. Disclosure of Interest: H. K. Hoiberg: None declared, A. G. Semb: None declared, A. P. Diamantopoulos: None declared, A. Kavanaugh: None declared, G. Haugeberg Grant/research support from: Unrestricted grant from Pfizer